Pendampingan Masyarakat Dalam Pembuatan & Mengembangkan Bisnis Olahan Keripik Bawang Pada Kelurahan Tampan Bonga - Marniati Marniati; Elisabeth Pali; Isak Pasulu; Wansi Tandi Ruru; Inestasia Inestasia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The Onion Chips Business is one of the snack food home industries as the basic ingredients for making them are easy to get on the market. The justification for selecting the business object offered is a type of food that is delicious, tasty and easy to obtain, nutritious and economical. There is no innovation in the management of the garlic business itself. So this activity aims to develop the garlic business into processed onion chips and provide new knowledge in marketing products in Tampan Bonga Village.